Coaches' philosophies on the transfer of strength training to elite sports performance. Issue 5 (October 2018) - Burnie, Louise; Barratt, Paul; Davids, Keith; Stone, Joseph; Worsfold, Paul; Wheat, Jon
The objective of the study was to explore coaches' philosophies regarding strength training (repetitive muscle actions against high loads) and the transfer of strength training to sports performance. Thirteen world class coaches and athletes from track cycling, Bicycle Moto-Cross (BMX), sprint kayaking, rowing and athletics sprinting were interviewed using an open-ended, semi-structured approach. Participants were asked about their coaching philosophies, design of athlete training programmes, strength training and its transfer to sports performance. A thematic analysis was conducted. Data trustworthiness was enhanced by methods of member checking and analyst triangulation. Coaches believed that task-specific strength is essential for sports performance. They reported that non-specific strength training ('traditional' gym-based strength exercises that are not specific to a sport movement) is important for increasing athletes' muscle size and strength. This is typically used in conjunction with resisted sport movement training (for example, increased resistance running, pedalling or rowing), believed to achieve an effective transfer of enhanced muscle strength to sports performance. Coaches described the transfer process as complex, with factors associated with fatigue and coordination having particular significance. The importance that coaches place on coordination is supported by a theoretical model that demonstrates increases in muscle strength from strength training may need to be accompanied with a change in inter-muscular coordination to improve sport performance. The idea that each athlete needs to adapt intermuscular coordination in response to a change in his/her unique set of 'organism constraints' (e.g. muscle strength) is well described by the theory of ecological dynamics and Newell's model of constraints.